Argentine journals of philosophy : visibility in international databases (Información, cultura y sociedad, 2005)
The article introduces periodical publication and addresses thequestions raised in connection with this format, focusing on Philosophy’s journalsin Argentina. Within Keresztesi’s framework of reference as regards the research/bibliography relationship, some quantitative methods to determine indicators ofrepresentativity, visibility and vacancy of Argentinean journals in Philosophyare applied. The research examines data available in both single-discipline and multidisciplinary international and Latin-American bases. Matters arising as aresult of our study are discussed and our conclusion is that the fewer the titles,the greater the visibility in international databases. Finally, we provide checkeddata for decision making in Philosophy information units.